(untitled) (Journal of the Society for Musicology in Ireland, 2024)
A review of Lorraine Byrne Bodley, Schubert: A Musical Wayfarer (New Haven and London: Yale University Press, 2023). ISBN 9780300204087, 736pp, 40 (hardback).